2020
DOI: 10.3390/nu12020525
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A and Phthalates in Diet: An Emerging Link with Pregnancy Complications

Abstract: Endocrine-disrupting chemicals (EDCs) are exogenous substances that are able to interfere with hormone action, likely contributing to the development of several endocrine and metabolic diseases. Among them, Bisphenol A (BPA) and phthalates contaminate food and water and have been largely studied as obesogenic agents. They might contribute to weight gain, insulin resistance and pancreatic β-cell dysfunction in pregnancy, potentially playing a role in the development of pregnancy complications, such as gestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 133 publications
(157 reference statements)
0
38
1
Order By: Relevance
“…It has been considered an endocrine disruptor by the European Chemicals Agency (ECHA 2017) [ 100 ] due to its estrogenic activity. BPA exposure in pregnancy is associated with negative outcomes, including impaired fetal growth and childhood adiposity [ 101 ].…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 99%
“…It has been considered an endocrine disruptor by the European Chemicals Agency (ECHA 2017) [ 100 ] due to its estrogenic activity. BPA exposure in pregnancy is associated with negative outcomes, including impaired fetal growth and childhood adiposity [ 101 ].…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 99%
“…Accordingly, a screening approach that takes into account the main GDM risk factors, such as obesity and previous GDM, might anticipate the diagnosis and prevent complications [11][12][13]. In addition, lifestyle, such as diet, physical activity or emerging environmental factors are likely to have an impact on the risk of developing GDM [13][14][15]. The identification of phenotypic classes associated with adverse outcomes, defined by the presence of some risk factors, turned out to be potentially useful in customizing and modulating the diagnostic and therapeutic approach in GDM [16,17].…”
Section: Introduction and Gdm Overviewmentioning
confidence: 99%
“…A growing body of evidence has further shown that BPA exposure, even at low doses, may have adverse effects on the outcomes of pregnancy in humans, resulting in potentially harmful conditions for both the mother and the offspring (e.g., affecting the normal development of the foetus and/or causing problems later in life) [ 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. There is also a correlation between BPA exposure and preeclampsia during pregnancy [ 74 , 75 ], which is characterized by newly diagnosed hypertension and proteinuria [ 76 ] and is associated with increased risk of both maternal mortality and health problems for the offspring later in life (e.g., obesity and T2DM) [ 76 , 77 ].…”
Section: Bpa and Comorbidities Predisposing To Severe Covid-19mentioning
confidence: 99%